Carbonyl hydrogenation catalyst as well as preparation method and application thereof

By using silica support and copper oxide active components in carbonyl hydrogenation catalyst, combined with metal additives and hydrothermal treatment, the problem of poor dispersion of active metals is solved, and efficient butanol selectivity and catalyst stability are achieved, improving the stability of the catalyst The activity and selectivity of the hydrogenation reaction.

CN119215909APending Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310755385.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing carbonyl hydrogenation catalysts have poor dispersion degree, low utilization efficiency, low activity, low selectivity and poor stability of hydrogenation products.

Method used

The carrier silica, active component copper oxide and metal active additives were used to prepare a catalyst with an oxygen vacancy content of more than 0.05 mmol/g after reduction activation. Combined with hydrothermal treatment and calcination technology, a high specific surface area and pore structure was prepared. The catalyst inhibits side reactions and the migration and aggregation of metal particles.

Benefits of technology

It improves the structural stability and hydrogenation activity of the catalyst, enhances the selectivity of butanol and the adsorption capacity of reactants, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215909A_ABST
    Figure CN119215909A_ABST
Patent Text Reader

Abstract

The present invention provides a carbonyl hydrogenation catalyst and a preparation method and application thereof, the catalyst comprises a carrier silica, an active component and a metal active auxiliary agent, the active component comprises copper oxide, and after the catalyst is reduced and activated, the oxygen vacancy content is 0.05 mmol / g or more. The catalyst is high in activity and good in selectivity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heterogeneous catalysis, and in particular to a carbonyl hydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] Butanol is an important solvent and organic chemical raw material, mainly used for preparing phthalates, aliphatic dibasic acid esters and phosphate plasticizers, widely used in various plastics and rubber products, and is also a raw material for manufacturing organic compounds such as butylamine and butyl lactate, and is a solvent for resins, paints, adhesives and a defoamer for mineral processing. At present, the main method for industrially producing butanol is to use a rhodium-catalyzed low-pressure carbonyl synthesis process, that is, propylene and synthesis gas are carbonylated in the presence of a homogeneous rhodium phosphine complex catalyst to generate butyraldehyde, and then the butyraldehyde is hydrogenated under the action of a hydrogenation catalyst to obtain butanol.

[0003] Industrially, the process routes for preparing butanol by hydrogenation of butyraldehyde mainly include gas phase method and liquid phase method. The liquid phase method uses nickel-based catalysts and multi-stage adiabatic fixed bed reactors with a reaction pressure of 4.0-5.0 MPa, and the raw material butyraldehyde participates in the hydrogenation reaction in a liquid state; the gas phase method uses copper-based catalysts and fixed bed tubular reactors with a reaction pressure of 0.4-0.7 MPa, and the raw materials participate in hydrogenation after being gasified. The gas phase method is widely used due to its low reaction pressure and simple process equipment. Most of the butanol production devices introduced in China use a gas phase hydrogenation process with Cu / Zn / Al components as hydrogenation catalysts. The performance of the hydrogenation catalyst in this process is the key factor in determining the efficiency of the hydrogenation reaction, so there are many reports on the development and research of Cu-based catalysts in patents and literature.

[0004] CN1381311A discloses a method for synthesizing a copper-zinc-aluminum catalyst by a coprecipitation method, and uses alkali metals / alkaline earth metals such as K, Ca, Na, Mg, and Ba as additives, so that the catalyst has good n-butyraldehyde hydrogenation efficiency and high n-butanol selectivity.

[0005] CN105107512A discloses a method for preparing a copper-based butyraldehyde hydrogenation catalyst by coprecipitation-spray drying. The preparation process of the catalyst is completed quickly within a few seconds, ensuring the uniformity of component distribution. The obtained catalyst particles have uniform size and good dispersibility, and can adapt to a gas space velocity of 15000h -1 , liquid space velocity 1h -1 reaction conditions.

[0006] CN1695802A discloses a method for preparing a copper-zinc aldehyde hydrogenation alcohol catalyst by a coprecipitation method using a two-step neutralization process and adding a metal auxiliary agent modification, wherein a portion of zinc is coprecipitated with an auxiliary aluminum, and the remaining zinc is coprecipitated with copper and the two precipitates are mixed to obtain a catalyst with a high specific surface area and a reasonable pore size distribution, and the catalyst has the characteristics of high hydrogenation activity and good thermal stability, and effectively improves the yield of the target product. The butyraldehyde gas phase hydrogenation catalyst disclosed in the above-mentioned technical patent is a copper catalyst containing aluminum oxide prepared by a coprecipitation method, and the biggest problem is that the dispersion of the active component is poor, the metal utilization rate is low, the thermal stability of the catalyst is general, and the by-product (butyl butyrate, butyl ether, etc.) generated by the acidity of the catalyst surface is high, and the butanol selectivity is reduced.

[0007] Therefore, it is necessary to explore carrier and auxiliary materials to optimize the surface acidity and alkalinity of the catalyst, increase the specific surface area of ​​the catalyst, improve the pore structure and promote the high dispersion of active metals, which plays a vital role in improving the hydrogenation activity, target product selectivity and long-term stability of butyraldehyde hydrogenation catalysts. Summary of the invention

[0008] The purpose of the present invention is to overcome the problems of poor dispersion of active metals, low utilization efficiency, low activity, low selectivity of hydrogenated products and poor stability in the prior art carbonyl hydrogenation catalyst, and to provide a carbonyl hydrogenation catalyst and a preparation method and application thereof. The carbonyl hydrogenation catalyst has a stable structure, good hydrogenation activity and good selectivity of hydrogenated products.

[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a carbonyl hydrogenation catalyst, which comprises: a carrier silica, an active component and a metal activator, wherein the active component comprises copper oxide, and after reduction activation of the catalyst, the oxygen vacancy content is above 0.05 mmol / g.

[0010] A second aspect of the present invention provides a method for preparing the catalyst of the present invention, the method comprising:

[0011] (1) evaporating ammonia in a first mixed solution containing a carrier source, a copper ammine complex, and a metal active promoter metal ammine complex to obtain a second mixed solution;

[0012] (2) The second mixed liquid is subjected to hydrothermal treatment, filtration, washing, drying, calcination, and molding to obtain a catalyst.

[0013] The third aspect of the present invention provides a use of the catalyst of the present invention in preparing alcohol from C2-C8 aldehyde.

[0014] Compared with the prior art, the present invention has the following advantages:

[0015] After reduction activation, the oxygen vacancy content of the carbonyl hydrogenation catalyst provided by the present invention is above 0.05 mmol / g. Meanwhile, the metal active additive, the carrier and the active component in the catalyst jointly promote the effective adsorption of the reactants and inhibit the occurrence of the dehydration side reaction, thereby reducing the generation of ester and ether by-products. Furthermore, the migration and aggregation of the active metal in the catalyst during the reaction process can be hindered to a certain extent, thereby avoiding the decrease in the catalyst activity due to the growth of metal particles and improving the structural stability of the catalyst. That is, the catalyst of the present invention has high activity, good selectivity and good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the H2-TPR diagram of the catalyst prepared in Example 1;

[0017] Figure 2 is the XRD pattern of the catalyst prepared in Example 1;

[0018] Figure 3 is the NH3-TPD diagram of the catalyst prepared in Example 1;

[0019] Figure 4 This is a working performance trend diagram of the catalyst prepared in Example 1. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0021] The invention provides a carbonyl hydrogenation catalyst, which comprises: carrier silicon dioxide, active components and metal active additives, wherein the active components comprise copper oxide, and after reduction activation, the oxygen vacancy content of the catalyst is above 0.05 mmol / g.

[0022] After reduction activation, the oxygen vacancy content of the carbonyl hydrogenation catalyst provided by the present invention is above 0.05 mmol / g. Meanwhile, the metal active additive, the carrier and the active component in the catalyst jointly promote the effective adsorption of the reactants and inhibit the occurrence of the dehydration side reaction, thereby reducing the generation of ester and ether by-products. To a certain extent, the migration and aggregation of the active metal in the catalyst during the reaction process can be hindered, the decrease in the catalyst activity caused by the growth of metal particles can be avoided, and the structural stability of the catalyst can be improved. That is, the catalyst of the present invention has high activity, good selectivity and good stability.

[0023] According to a particularly preferred embodiment of the present invention, after reduction activation of the catalyst, the oxygen vacancy content is 0.06-0.12 mmol / g, for example, it can be 0.06 mmol / g, 0.07 mmol / g, 0.08 mmol / g, 0.09 mmol / g, 0.10 mmol / g, 0.11 mmol / g, 0.12 mmol / g.

[0024] According to a particularly preferred embodiment of the present invention, in the XRD spectrum of the catalyst, characteristic peaks exist at 2θ=35.4±1° and 38.2±1°.

[0025] According to a preferred embodiment of the present invention, the reduction activation is carried out in a reducing atmosphere, and preferably the reducing atmosphere is selected from H2 atmosphere and / or CO atmosphere.

[0026] According to a preferred embodiment of the present invention, the reduction activation conditions include: temperature of 180-250° C. and time of 8-12 h.

[0027] According to a particularly preferred embodiment of the present invention, the metal active auxiliary agent is selected from oxides of lanthanide metals and / or Group IVB metals.

[0028] According to a particularly preferred embodiment of the present invention, the metal active additive is selected from oxides of lanthanide metals and Group IVB metals. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0029] In the present invention, there is no particular requirement for the mass ratio of the oxide of the lanthanide metal to the oxide of the Group IVB metal in the metal activating agent. According to a particularly preferred embodiment of the present invention, the mass ratio of the oxide of the lanthanide metal to the oxide of the Group IVB metal in the metal activating agent is 0.2-5: 1. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0030] In the present invention, all lanthanide metals can be used in the present invention. According to a particularly preferred embodiment of the present invention, the lanthanide metal is selected from at least one of La, Ce, and Pr.

[0031] According to a particularly preferred embodiment of the present invention, the lanthanide metal is selected from La and / or Ce. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0032] In the present invention, all Group IVB metals can be used in the present invention. According to a particularly preferred embodiment of the present invention, the Group IVB metal is selected from Ti and / or Zr.

[0033] According to a particularly preferred embodiment of the present invention, the Group IVB metal is selected from Ti. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0034] According to a preferred embodiment of the present invention, the carrier is silicon dioxide modified by at least one modifier selected from molybdenum oxide, manganese oxide, iron oxide, cobalt oxide and nickel oxide; preferably, the content of the modifier in the modified silicon dioxide is 3-25wt%. By adopting the above preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0035] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the content of each component of the catalyst. According to a particularly preferred embodiment of the present invention, the content of copper oxide in the catalyst is 20-50%; the content of the metal active additive is 9-35%; and the content of the carrier is 15-70%, based on the total mass of the catalyst.

[0036] In the present invention, as long as the purpose of the present invention can be achieved, there is no special requirement for the content of each component of the catalyst. According to a particularly preferred embodiment of the present invention, the content of copper oxide in the catalyst is 20-40% based on the total mass of the catalyst; the content of the active agent is 9-25%; and the content of the carrier is 35-70%. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0037] According to a particularly preferred embodiment of the present invention, the specific surface area of ​​the catalyst is 150-400m 2 g -1 , preferably 180-300m 2 g -1 .

[0038] According to a particularly preferred embodiment of the present invention, the pore volume of the catalyst is 0.3-1.0 cm 2 g -1 , preferably 0.4-0.7cm 2 g -1 .

[0039] According to a particularly preferred embodiment of the present invention, the most probable pore diameter of the catalyst is 6.0-10.0 nm, preferably 8.0-10.0 nm.

[0040] According to a particularly preferred embodiment of the present invention, the pore volume of the catalyst with pores having a pore diameter of 6-10 nm accounts for 50-95%, preferably 60-90%, of the total pore volume.

[0041] According to a particularly preferred embodiment of the present invention, the average grain size of the copper oxide is 3-15 nm, preferably 6-12 nm.

[0042] According to a particularly preferred embodiment of the present invention, the total surface acidity of the catalyst is no more than 0.1 mmol / g, preferably no more than 0.01-0.08 mmol / g, based on the amount of ammonia chemical adsorption. By adopting the above-mentioned preferred embodiment, the activity, selectivity and stability of the catalyst can be further improved.

[0043] According to a particularly preferred embodiment of the present invention, the reduction temperature of the copper oxide in the catalyst is not higher than 220°C, preferably not higher than 200°C, more preferably 150-200°C.

[0044] The present invention provides a method for preparing the catalyst of the present invention, the method comprising:

[0045] (1) evaporating ammonia in a first mixed solution containing a carrier source, a copper ammine complex, and a metal active promoter metal ammine complex to obtain a second mixed solution;

[0046] (2) The second mixed liquid is subjected to hydrothermal treatment, filtration, washing, drying, calcination, and molding to obtain a catalyst.

[0047] The catalyst of the present invention can be prepared by the method of the present invention, and the prepared catalyst has a high specific surface area and pore volume, which is conducive to the high dispersion of active metals on the surface of the carrier, realizes the efficient utilization of metal components, reduces the production of by-products, provides more specific adsorption sites for carbonyl groups in reactant molecules, and improves the adsorption capacity of the catalyst for gas-phase reactants and the structural stability, activity and selectivity of the catalyst.

[0048] In the present invention, the preparation method of the first mixed solution can be a conventional method in the art. According to a particularly preferred embodiment of the present invention, the preparation method of the first mixed solution includes mixing and dissolving a carrier source, a copper source, a metal activator source and an ammonia source to obtain the first mixed solution. Preferably, the copper source and the metal activator source are first dissolved, and then the ammonia source is added, and then the carrier source is added to obtain the first mixed solution. By adopting the above-mentioned preferred method, the performance of the prepared catalyst can be further improved.

[0049] According to a particularly preferred embodiment of the present invention, the ammonia source is aqueous ammonia and / or ammonia gas, wherein the concentration of the aqueous ammonia is 10-28 wt %.

[0050] According to a particularly preferred embodiment of the present invention, the dissolving solvent is selected from at least one of water, methanol and ethanol.

[0051] According to a particularly preferred embodiment of the present invention, the difference between the pH of the first mixed solution and the pH of the second mixed solution is 4-6.

[0052] According to a particularly preferred embodiment of the present invention, the pH of the first mixed solution is 11-12.

[0053] According to a particularly preferred embodiment of the present invention, the pH of the second mixed solution is 6-7.

[0054] According to a particularly preferred embodiment of the present invention, the evaporation conditions include: a temperature of 70-90°C, preferably 75-85°C.

[0055] According to a particularly preferred embodiment of the present invention, the conditions of the hydrothermal treatment include: a temperature of 130-150°C, preferably 140-150°C.

[0056] According to a particularly preferred embodiment of the present invention, the conditions of the hydrothermal treatment include: a time of 24-48 hours.

[0057] According to a particularly preferred embodiment of the present invention, the drying conditions include: temperature 80-120° C.; time 10-12 h.

[0058] In the present invention, the calcination conditions can be selected according to conventional techniques in the art. According to a particularly preferred embodiment of the present invention, the calcination conditions include: a temperature of 300-400° C.; and / or a time of 2-8 h.

[0059] In the present invention, the type of the carrier can be selected from a wide range. According to a particularly preferred embodiment of the present invention, the carrier source is selected from an organic silicon source and / or an inorganic silicon source, preferably at least one of silica sol, tetraethyl silicate, silicon dioxide powder and sodium silicate.

[0060] According to a particularly preferred embodiment of the present invention, the carrier source is a carrier source modified by at least one modifier selected from the group consisting of molybdenum oxide, manganese oxide, iron oxide, cobalt oxide and nickel oxide.

[0061] According to a particularly preferred embodiment of the present invention, the modification method comprises: mixing a modification aid precursor, an optional additive and a carrier source, and then removing the solvent, drying and calcining.

[0062] According to a particularly preferred embodiment of the present invention, the additive is selected from citric acid and / or ethylenediaminetetraacetic acid.

[0063] According to a particularly preferred embodiment of the present invention, the molding method includes tableting and / or extrusion, and optionally, crushing and screening are performed after molding to obtain a granular catalyst with a particle size of 10-20 mesh.

[0064] The present invention provides an application of the catalyst of the present invention in preparing alcohol from C2-C8 aldehydes, more preferably in preparing butanol from butyraldehyde by hydrogenation.

[0065] The catalyst provided by the present invention is suitable for aldehyde hydrogenation to alcohol, and is particularly suitable for n-butyraldehyde hydrogenation to butanol, and has high butanol selectivity. The catalyst can expose abundant surface oxygen defects under the reducing atmosphere of the hydrogenation reaction, provide more specific adsorption sites for the carbonyl groups in the reactant molecules, and improve the adsorption capacity of the catalyst to the reactants. At the same time, the presence of the auxiliary agent can also hinder the migration and aggregation of active metals in the catalyst during the reaction process to a certain extent, avoid the decrease in catalyst activity caused by the growth of metal particles, and improve the structural stability of the catalyst.

[0066] The invention provides a method for preparing butanol by hydrogenating butyraldehyde, which comprises: contacting butyraldehyde raw material with hydrogen in the presence of a catalyst; the catalyst is the hydrogenation catalyst of the invention.

[0067] In the method of the present invention, the butyraldehyde raw material conversion rate is high and the selectivity is high.

[0068] In the present invention, the conditions of the contact reaction can be conventionally selected in the art. According to a preferred embodiment of the present invention, according to a particularly preferred embodiment of the present invention, the conditions of the contact reaction include: a reaction pressure of 0.4-0.6 MPa, a reaction temperature of 100-160° C., a H2 / aldehyde molar ratio of 15-30, and a butyraldehyde liquid feed space velocity of 0.4-1 h -1 .

[0069] According to a particularly preferred embodiment of the present invention, the contact reaction conditions include: reaction pressure of 0.4-0.5 MPa, temperature of 110-140°C, H2 / aldehyde molar ratio of 15-25, butyraldehyde liquid feed space velocity of 0.4-0.8h -1 .

[0070] According to a particularly preferred embodiment of the present invention, the catalyst is subjected to reduction activation treatment before use, and the reduction activation conditions include: temperature 180-250°C, preferably 200-240°C; and / or time 8-12h, preferably 8-10h.

[0071] In order to make the present invention easier to understand, the present invention will be described in detail below in conjunction with examples. These examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials involved in the examples are all commercially available unless otherwise specified.

[0072] In the present invention, H2-TPR is carried out on a BELCATⅡ, MicrotracBEL instrument, with a reducing gas of 5 vol% H2 / Ar. Before the sample is tested, it is first purged in Ar at 200°C for 2h, and then the sample TPR curve is collected from room temperature to 700°C, with a heating rate of 5°C / min.

[0073] In the present invention, XRD spectrum: Philip X'pert Pro diffractometer is used to collect XRD spectrum of the catalyst, the X-ray radiation source is Cu target Kα ray (λ=0.15408nm) filtered by Ni filter, the collection step is 0.06° / s, the X-ray tube operating voltage is 40kV, and the current is 40mA.

[0074] The average CuO grain size was calculated based on the XRD data using the Scherrer formula.

[0075] In the present invention, the pore structure properties of the sample were tested using a Micromeritics ASAP-3020 physical adsorption instrument. The sample was degassed at 300°C for 3 hours before the test, and the test was performed at liquid nitrogen temperature (-196°C). The specific surface area of ​​the sample was calculated by the Brunauer-Emmett-Teller (BET) multilayer physical adsorption model, and the pore size distribution was obtained by the Barrett-Joyner-Halenda method.

[0076] In the present invention, the amount of acid on the catalyst surface is determined by the NH3-TPD method: 10 vol% NH3 / Ar is performed on a BELCATⅡ, MicrotracBEL instrument. Before the sample is tested, it is first purged in Ar at 200°C for 2 hours, and after cooling to 100°C, the sample adsorbs 10 vol% NH3 / Ar for 30 minutes, and then switched to Ar purging for 1 hour, and the TPD curve is collected from 100°C to 600°C, with a heating rate of 5°C / min.

[0077] In the present invention, the oxygen vacancy content is estimated from the content of low-valent elements in the auxiliary oxide in the sample, wherein the content of low-valent auxiliary oxide is measured by XPS: XPS test is performed using a PHI 5000VersaProbe system, and the X-ray source is a monochromatic Al target Kα line (1486.6eV). All sample binding energies are corrected using an external source C1s (284.6eV) to compensate for the surface charging effect of the sample.

[0078] Example 1

[0079] Weigh 47.157g of copper nitrate and 9.474g of cerium nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 11, continue stirring for 30min, then weigh 75g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 6 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed 3 times with deionized water. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace, and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder, and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-1.

[0080] After testing: the specific surface area of ​​BHC-1 is 242m 2 g -1 , the total pore volume is 0.55cm 3 g -1 The most probable pore size is 8.2 nm, and the pore volume with a pore size of 6-10 nm accounts for 74% of the total pore volume; the average grain size of copper oxide is 7.4 nm, and the acid content is 0.04 mmol g -1 After reduction activation, the oxygen vacancy is 0.10 mmol g -1 .

[0081] Figure 1 This is the H2-TPR spectrum of BHC-1. It can be seen that the sample shows a reduction peak belonging to copper oxide, and the reduction temperature is about 165°C.

[0082] Figure 2 This is the XRD diagram of BHC-1. It can be seen that the sample has characteristic peaks at 2θ=35.7° and 38.3°.

[0083] Figure 3 This is the NH3-TPD spectrum of BHC-1. The results show a broad desorption peak in the range of 100-300 degrees with low intensity, indicating that the surface of the sample is mainly weakly acidic.

[0084] Example 2

[0085] Weigh 47.157g of copper nitrate and 9.973g of lanthanum nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 12, continue stirring for 30min, then weigh 75g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed solution in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed solution in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water for 3 times. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace, and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder, and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-2.

[0086] After testing: the specific surface area of ​​BHC-2 is 226m 2 g -1 , the total pore volume is 0.51cm 3 g -1 The most probable pore size is 8.4 nm, and the pores with a pore size of 6-10 nm account for 76% of the total pore volume; the average grain size of copper oxide is 7.6 nm, and the acid content is 0.03 mmol g -1 After reduction activation, the oxygen vacancy is 0.05 mmol g -1 The XRD pattern of BHC-2 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 166 °C attributed to copper oxide.

[0087] Example 3

[0088] Weigh 47.157g of copper nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water by mass, adjust the pH value of the solution to 11, and continue stirring for 30min. Weigh 86.699g of TEOS and 21.299g of n-butyl titanate in a 250ml beaker, first add 50g of anhydrous ethanol to dilute, add to the above solution, and continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during the period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 7 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water for 3 times. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace and calcined at 350° C. in air for 4 h. The obtained solid was ground into powder and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-3.

[0089] After testing: the specific surface area of ​​BHC-3 is 296m 2 g -1 , the total pore volume is 0.66 cm 3 g -1 The most probable pore size is 7.2 nm, and the pore volume with a pore size of 6-10 nm accounts for 89% of the total pore volume; the average grain size of copper oxide is 6.5 nm, and the acid content is 0.04 mmol g -1 After reduction activation, the oxygen vacancy is 0.07 mmol g -1 The XRD pattern of BHC-3 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 157 °C attributed to copper oxide.

[0090] Example 4

[0091] Weigh 47.157g of copper nitrate and 9.474g of cerium nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water by mass, adjust the pH value of the solution to 12, continue stirring for 30min, weigh 86.699g of TEOS in a 250ml beaker, first add 50g of anhydrous ethanol to dilute, then add to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during the period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 6 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed 3 times with deionized water. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-4.

[0092] After testing: the specific surface area of ​​BHC-4 is 274m 2 g -1 , the total pore volume is 0.58 cm 3 g -1 The most probable pore size is 7.6 nm, and the pores with a pore size of 6-10 nm account for 76% of the total pore volume; the average grain size of copper oxide is 7.1 nm, and the acid content is 0.02 mmol g -1 After reduction activation, the oxygen vacancy is 0.08 mmol g -1 The XRD pattern of BHC-4 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 165 °C attributed to copper oxide.

[0093] Example 5

[0094] Weigh 47.157g of copper nitrate and 5.273g of cerium nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water by mass, adjust the pH value of the solution to 11, and continue stirring for 30min. Weigh 30g of silicon dioxide powder and 11.299g of n-butyl titanate in a 250ml beaker, first add 50g of anhydrous ethanol to dilute, add to the above solution, and continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during the period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 6 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water for 3 times. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-5.

[0095] After testing: the specific surface area of ​​BHC-5 is 189m 2 g -1 , the total pore volume is 0.42 cm 3 g -1 The most probable pore size is 9.8 nm, and the pore volume with a pore size of 6-10 nm accounts for 79% of the total pore volume; the average grain size of copper oxide is 10.6 nm, and the acid content is 0.06 mmol g -1 After reduction activation, the oxygen vacancy is 0.07 mmol g -1 The XRD pattern of BHC-5 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 188 °C attributed to copper oxide.

[0096] Example 6

[0097] Weigh 47.157g of copper nitrate and 12.642g of praseodymium nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 11, continue stirring for 30min, then weigh 75g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 6 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed 3 times with deionized water. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace, and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-6.

[0098] After testing: the specific surface area of ​​BHC-6 is 216m 2 g -1 , the total pore volume is 0.46 cm 3 g -1 The most probable pore size is 8.6 nm, and the pore volume with a pore size of 6-10 nm accounts for 72% of the total pore volume; the average grain size of copper oxide is 8.3 nm, and the acid content is 0.04 mmol g -1 After reduction activation, the oxygen vacancy is 0.05 mmol g -1 The XRD pattern of BHC-6 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 177 °C attributed to copper oxide.

[0099] Example 7

[0100] Weigh 47.157g of copper nitrate and 9.474g of cerium nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 11, continue stirring for 30min, then weigh 150g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 6 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water for 3 times. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-7.

[0101] After testing: the specific surface area of ​​BHC-7 is 266m 2 g -1 , the total pore volume is 0.61cm 3 g -1 The most probable pore size is 8.3 nm, and the pore volume with a pore size of 6-10 nm accounts for 72% of the total pore volume; the average grain size of copper oxide is 7.9 nm, and the acid content is 0.05 mmol g -1 After reduction activation, the oxygen vacancy is 0.08 mmol g -1 The XRD pattern of BHC-7 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 171 °C attributed to copper oxide.

[0102] Example 8

[0103] Weigh 20.583g of 50wt% manganese nitrate solution and 13.246g of citric acid in a beaker, add 100g of deionized water and stir to dissolve, then add 30g of silica powder to the solution, and continue stirring the mixture for 2h. Transfer the mixture to an 80℃ oil bath and heat to evaporate the water, place the solid in a 100℃ oven to dry for 12h, and then place it in a tubular furnace and calcine at 450℃ for 4h in a nitrogen atmosphere to obtain a modified silica carrier.

[0104] Weigh 47.157g of copper nitrate and 9.474g of cerium nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water by mass, adjust the pH value of the solution to 11, continue stirring for 30min, then weigh 30g of modified silicon dioxide and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 6 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed 3 times with deionized water. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace, and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-8.

[0105] After testing: the specific surface area of ​​BHC-8 is 196m 2 g -1 , the total pore volume is 0.41cm 3 g -1 The most probable pore size is 9.8 nm, and the pore volume with a pore size of 6-10 nm accounts for 62% of the total pore volume; the average grain size of copper oxide is 9.1 nm, and the acid content is 0.08 mmol g -1 After reduction activation, the oxygen vacancy is 0.07 mmol g -1 The XRD pattern of BHC-8 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 184 °C attributed to copper oxide.

[0106] Example 9

[0107] Weigh 47.157g of copper nitrate and 21.935g of zirconium nitrate in a 500ml beaker, add 300g of deionized water and stir to dissolve the metal salt, then gradually and slowly add 25% ammonia water, adjust the pH value of the solution to 11, continue stirring for 30min, then weigh 75g of 40% silica sol, and add it to the above solution, continue stirring and mixing for 4h to obtain the first mixed solution. Heat the first mixed solution to 80°C, evaporate the ammonia in the solution, add 30g of deionized water 3 times during this period to ensure that the solution is not evaporated to dryness, and stop heating when the pH value of the solution reaches 6 to obtain the second mixed solution. The second mixed liquid in the beaker was transferred to a 250 ml high pressure hydrothermal autoclave, and placed in a 150° C. oven for hydrothermal heating for 24 h. Finally, the hydrothermal autoclave was taken out and cooled to room temperature. The mixed liquid in the hydrothermal autoclave was filtered, and the filter cake was washed with deionized water for 3 times. The filter cake was dried in an oven at 100° C. for 8 h, ground into powder, placed in a muffle furnace, and calcined in air at 350° C. for 4 h. The obtained solid was ground into powder and tableted using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-9.

[0108] After testing: the specific surface area of ​​BHC-9 is 231m 2 g -1 , the total pore volume is 0.55cm 3 g -1 The most probable pore size is 9.1 nm, and the pores with a pore size of 6-10 nm account for 62% of the total pore volume; the average grain size of copper oxide is 8 nm, and the acid content is 0.06 mmol g -1 After reduction activation, the oxygen vacancy is 0.05 mmol g -1 The XRD pattern of BHC-9 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 174 °C attributed to copper oxide.

[0109] Example 10

[0110] Weigh 47.157g copper nitrate and 9.474g cerium nitrate in a 250ml beaker, add 100g deionized water and stir until completely dissolved, then transfer all the solution to a stirred reactor, set the heating temperature to 60°C, and the stirring rate to 150rpm; then weigh 37.206g ammonium carbonate in a 250ml beaker, add 100g deionized water and stir until completely dissolved, then transfer the solution to a measuring cylinder and dilute to 250ml; weigh 86.699g TEOS in a 250ml beaker, first add 50g anhydrous ethanol to dilute, then transfer the solution to a measuring cylinder, and then add anhydrous ethanol to dilute to 250ml. Use a peristaltic pump to flow the TEOS solution and the ammonium carbonate solution into the stirred reactor, maintain the temperature and speed in the stirred reactor, where the flow rate of the TEOS solution is 10ml / min, and the flow rate of the ammonium carbonate solution is 10ml / min. After the addition was completed, the slurry in the reactor was aged at 60°C for 6 hours, then the slurry was filtered, the filter cake was washed with deionized water 3 times, transferred to a 100°C oven for drying for 12 hours, and then placed in a muffle furnace for calcination at 350°C for 4 hours. The obtained solid was ground into powder and pressed into tablets using an electric tablet press at a pressure of 10 MPa. The catalyst tablets were crushed and sieved to obtain a granular catalyst with a particle size of 10-20 mesh, which was recorded as BHC-10.

[0111] After testing: the specific surface area of ​​BHC-10 is 172m 2 g -1 , the total pore volume is 0.30cm 3 g -1 The most probable pore size is 6.2 nm, and the pore volume with a pore size of 6-10 nm accounts for 50% of the total pore volume; the average grain size of copper oxide is 4 nm, and the acid content is 0.1 mmol g -1 After reduction activation, the oxygen vacancy is 0.05 mmol g -1 The XRD pattern of BHC-10 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 155 °C attributed to copper oxide.

[0112] Embodiment 11

[0113] The same as Example 1, except that an equal amount of modified silica carrier is used to replace silica sol, and the carrier preparation includes: weighing 30.292g of ferric nitrate nonahydrate and 13.246g of citric acid in a beaker, adding 100g of deionized water and stirring to dissolve, then adding 20g of mesoporous silica SBA-15 to the solution, and stirring the mixed solution for 2h. The mixed solution is transferred to an 80°C oil bath and heated to evaporate the water, the solid is placed in a 100°C oven to dry for 12h, and then placed in a tubular furnace and calcined at 450°C for 4h in a nitrogen atmosphere to obtain a modified silica carrier.

[0114] The obtained catalyst was recorded as BHC-11.

[0115] After testing: the specific surface area of ​​BHC-11 is 209m 2 g -1 , with a total pore volume of 0.5 cm 3 g -1 The most probable pore size is 9.5 nm, and the pore volume with a pore size of 6-10 nm accounts for 66% of the total pore volume; the average grain size of copper oxide is 8.6 nm, and the acid content is 0.06 mmol g -1 After reduction activation, the oxygen vacancy is 0.09 mmol g -1 The XRD pattern of BHC-11 is Figure 2 Similarly, the H2-TPR spectrum showed a reduction peak temperature of 180 °C attributed to copper oxide.

[0116] Comparative Example 1

[0117] The same as Example 1, except that the mass of the silicon source calculated as silicon oxide is replaced by the same mass of the aluminum source calculated as aluminum oxide, to obtain a catalyst, which is recorded as DB-1.

[0118] After testing: the specific surface area of ​​DB-1 is 84m 2 g -1 , the total pore volume is 0.13 cm 3 g -1 The most probable pore size is 18.9 nm, and the pore volume with a pore size of 6-10 nm accounts for 33% of the total pore volume; the average grain size of copper oxide is 14.4 nm, and the acid content is 0.23 mmol g -1 After reduction activation, the oxygen vacancy is 0.04 mmol g -1 The H2-TPR spectrum of DB-1 showed a reduction peak temperature of 232°C, which was attributed to copper oxide.

[0119] Comparative Example 2

[0120] The same as Example 1, except that no cerium nitrate was added, to obtain a catalyst, which was recorded as DB-2.

[0121] After testing: the specific surface area of ​​DB-2 is 168m 2 g -1 , the total pore volume is 0.27 cm 3 g -1 The most probable pore size is 15.2 nm, and the pore volume with a pore size of 6-10 nm accounts for 36% of the total pore volume; the average grain size of copper oxide is 12.5 nm, and the acid content is 0.13 mmol g -1 After reduction activation, the oxygen vacancy is 0.02 mmol g -1 The H2-TPR spectrum of DB-2 showed that the reduction peak temperature attributed to copper oxide was 216°C.

[0122] Comparative Example 3

[0123] The same as Example 1, except that the mass of cerium nitrate calculated as cerium oxide is replaced by the same mass of magnesium nitrate calculated as magnesium oxide, to obtain a catalyst, which is recorded as DB-3.

[0124] After testing: the specific surface area of ​​DB-3 is 224m 2 g -1 , the total pore volume is 0.43 cm 3 g -1 The most probable pore size is 11.6 nm, and the pores with a pore size of 6-10 nm account for 45% of the total pore volume; the average grain size of copper oxide is 11.1 nm, and the acid content is 0.06 mmol g -1 After reduction activation, the oxygen vacancy is 0.02 mmol g -1 The H2-TPR spectrum of DB-3 showed that the reduction peak temperature attributed to copper oxide was 209°C.

[0125] Example 12

[0126] 10 ml of the catalyst prepared in the above examples and comparative examples was loaded into a solid bed reactor, first heated to 120°C in a nitrogen atmosphere for 4 hours to remove physically adsorbed water on the catalyst surface, and then cooled to room temperature. The atmosphere was then switched to hydrogen, heated to 230°C and maintained for 8 hours to obtain a reduction-activated catalyst. The performance of the n-butyraldehyde hydrogenation catalyst was then evaluated under the experimental conditions of a bed temperature of 120°C, a reaction pressure of 0.5 MPa, and a n-butyraldehyde liquid space velocity of 0.4 h -1 , hydrogen-to-aldehyde ratio 20:1, the hydrogenation product was analyzed by gas chromatography, the chromatographic detector was FID, and the experimental results are shown in Table 1.

[0127] Embodiment 13

[0128] The catalyst prepared in Example 1 was used in the same manner as in Example 12, except that octenal was used as the reaction raw material and the reaction bed temperature was 190° C. The measured conversion rate and selectivity were 98.7% and 99.3%, respectively.

[0129] Embodiment 14

[0130] 10 ml of the catalyst obtained in Example 1 was loaded into a solid bed reactor, first heated to 120°C in a nitrogen atmosphere for 4 hours to remove physically adsorbed water on the catalyst surface, and then cooled to room temperature. The atmosphere was then switched to hydrogen, heated to 230°C and maintained for 8 hours to obtain a reduction-activated catalyst, which was used in situ for the evaluation of butyraldehyde hydrogenation stability. The experimental conditions were a bed temperature of 120°C, a reaction pressure of 0.5 MPa, and a liquid space velocity of n-butyraldehyde of 0.4 h -1, hydrogen-formaldehyde ratio 20:1, reaction time 800h. The hydrogenation product was analyzed by gas chromatography, the chromatographic detector was FID, and the experimental results are shown in Figure 4 .

[0131] It can be seen that the catalyst of the present application can maintain high activity and high selectivity for 800 hours, and has better stability than the catalysts prepared in Comparative Examples 1-3 (stable operation for 300-400 hours).

[0132] Table 1

[0133] serial number Butyraldehyde conversion rate / % n-Butanol selectivity / % BHC-1 98.8 99.4 BHC-2 98.4 99.3 BHC-3 98.7 99.4 BHC-4 98.5 99.2 BHC-5 99.9 99.7 BHC-6 97.3 99.0 BHC-7 98.0 99.1 BHC-8 99.9 99.6 BHC-9 96.6 98.9 BHC-10 96.5 98.2 BHC-11 99.5 99.8 DB-1 83.2 81.4 DB-2 86.1 96.1 DB-3 90.4 94.3

[0134] It can be seen from the results in the examples, comparative examples and Table 1 that the catalysts prepared by the present invention have excellent n-butyraldehyde hydrogenation performance under the same process conditions, and the silicon oxide component used in the catalyst avoids the presence of too many acid sites on the surface, reduces the occurrence of dehydration side reactions, and makes the catalysts show good product selectivity. In addition, the presence of the additive is conducive to adjusting the adsorption properties of the catalyst surface to the reactants, further improving the hydrogenation activity and butanol selectivity of the catalyst.

[0135] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A carbonyl hydrogenation catalyst, characterized in that: The catalyst comprises: carrier silicon dioxide, active components and metal active additives, wherein the active components include copper oxide, After reduction activation, the catalyst has an oxygen vacancy content of more than 0.05 mmol / g.

2. The catalyst according to claim 1, wherein After reduction activation, the catalyst has an oxygen vacancy content of 0.06-0.12 mmol / g; and / or In the XRD spectrum of the catalyst, characteristic peaks exist at 2θ=35.4±1° and 38.2±1°; and / or The metal active agent is selected from oxides of lanthanide metals and / or Group IVB metals; preferably, the metal active agent is selected from oxides of lanthanide metals and Group IVB metals; More preferably, the mass ratio of the oxide of the lanthanide metal to the oxide of the Group IVB metal in the metal activating agent is 0.2-5:

1.

3. The catalyst according to claim 1 or 2, wherein The lanthanide metal is selected from at least one of La, Ce and Pr, preferably La and / or Ce; and / or The Group IVB metal is selected from Ti and / or Zr, preferably Ti; and / or The carrier is silicon dioxide modified by at least one modifier selected from molybdenum oxide, manganese oxide, iron oxide, cobalt oxide and nickel oxide; Preferably, the content of the modifier in the modified silicon dioxide is 3-25wt%.

4. The catalyst according to any one of claims 1 to 3, wherein In the catalyst, based on the total mass of the catalyst, the content of copper oxide is 20-50%, preferably 20-40%; the content of metal active additive is 9-35%, preferably 9-25%; and the content of carrier is 15-70%, preferably 35-70%.

5. The catalyst according to any one of claims 1 to 4, wherein The specific surface area of ​​the catalyst is 150-400m 2 g -1 , preferably 180-300m 2 g -1 ; and / or The pore volume of the catalyst is 0.3-1.0 cm 2 g -1 , preferably 0.4-0.7cm 2 g -1 ; and / or The most probable pore size of the catalyst is 6.0-10.0 nm, preferably 8.0-10.0 nm; and / or The pore volume of the catalyst with a pore size of 6-10 nm accounts for 50-95%, preferably 60-90% of the total pore volume; and / or The average grain size of the copper oxide is 3-15 nm, preferably 6-12 nm.

6. The catalyst according to any one of claims 1 to 5, wherein The total surface acidity of the catalyst is no more than 0.1 mmol / g, preferably 0.01-0.08 mmol / g, calculated as ammonia chemical adsorption; and / or The reduction temperature of the copper oxide in the catalyst is not higher than 220°C, preferably 150-200°C.

7. The method for preparing the catalyst according to any one of claims 1 to 6, characterized in that: The method includes: (1) evaporating ammonia in a first mixed solution containing a carrier source, a copper ammine complex, and an active promoter metal ammine complex to obtain a second mixed solution; (2) The second mixed solution is subjected to hydrothermal treatment, filtration, washing, drying, calcination, and molding to obtain a catalyst; Preferably, the preparation method of the first mixed solution comprises mixing and dissolving a carrier source, a copper source, a metal active additive source and an ammonia source; More preferably, the copper source and the metal active additive source are first dissolved, and then the ammonia source is added, and then the carrier source is added, and mixed to obtain a first mixed solution; More preferably, the ammonia source is aqueous ammonia and / or ammonia gas, wherein the concentration of aqueous ammonia is 10-28 wt %; and / or The dissolving solvent is selected from at least one of water, methanol and ethanol.

8. The preparation method according to claim 7, wherein: The difference between the pH of the first mixed solution and the pH of the second mixed solution is 4-6; preferably, The pH of the first mixed solution is 11-12; and / or The pH of the second mixed solution is 6-7.

9. The preparation method according to claim 7 or 8, wherein: The evaporation conditions include: a temperature of 70-90°C, preferably 75-85°C; and / or The conditions of the hydrothermal treatment include: a temperature of 130-150° C., preferably 140-150° C.; and / or a time of 24-48 hours; and / or The drying conditions include: temperature of 80-120°C; and / or time of 10-12h; and / or The calcination conditions include: a temperature of 300-400° C.; and / or a calcination time of 2-8 hours.

10. The preparation method according to claims 7-9, wherein: The carrier source is selected from an organic silicon source and / or an inorganic silicon source, preferably at least one of silica sol, tetraethyl silicate, and silicon dioxide powder; more preferably, it is a carrier source modified by at least one modifier selected from molybdenum oxide, manganese oxide, iron oxide, cobalt oxide, and nickel oxide.

11. Use of the catalyst according to any one of claims 1 to 6 in preparing alcohol from C2-C8 aldehydes, more preferably in preparing butanol by hydrogenation of butyraldehyde.